Reinterpreting Marital Maintenance: A Maqāṣid al-Sharī’ah Study on Skincare and Cosmetics Consumption in Indonesia and Algeria - Barkah, Mochamad Riskana; Rouf, Abd. (KALOSARA: Family Law Review, 2025)
In Islamic law, research on marital maintenance (nafkah) has traditionally focused on clothing, food, and shelter. In contrast, the role of skincare and cosmetics as part of a wife’s maintenance remains underexplored, especially in a comparative context between Indonesia and Algeria. Prior studies limit nafkah to basic needs, overlooking emerging consumption patterns shaped by health awareness and modern self-care practices. This study addresses this gap by reinterpreting nafkah through the lens of maqāṣid al-sharī’ah and ‘urf, employing a normative-comparative approach. The research examines classical and contemporary fiqh sources, national regulations—including Indonesia’s Marriage Law and Compilation of Islamic Law, and Algeria’s Code de la Famille—and recent socio-cultural dynamics in both countries. Findings suggest that skincare, due to its preventive and health-related functions, aligns with ḥifẓ al-nafs (protection of life/health) and ḥifẓ al-’irḍ (protection of dignity), and thus qualifies as obligatory nafkah bil-ma’rūf. Cosmetics are conditional, required only if they were part of the wife’s pre-marital habits (‘urf khāṣṣ) or requested by the husband, falling under taḥsīniyyāt. Comparative analysis highlights differences in family law orientation: Indonesia tends toward a formalistic approach, whereas Algeria adopts an adaptive framework emphasizing ‘urf through the Maliki school. This study contributes to contemporary Islamic family law discourse by illustrating how consumption culture, gender expectations, and modern health practices intersect with marital obligations.   Keywords: Maqāṣid al-Sharī’ah, Reinterpretation of Nafkah, Skincare and Cosmetics, ‘Urf